Peripheral Vascular Injuries in Extremity Trauma, Single-center Experience - Parajuli, Nirajan Prasad; Khan, MI; Yadav, KK; Shah, RK (Nepal Orthopaedic Association Journal, 2021)
Background: Peripheral vascular injuries are relatively uncommon and constitute 2-4% of cases presenting in the Orthopaedic Department. Managing vascular injuries in the Provincial hospital of Nepal is very challenging when they occur in combination with nerve injuries, fractures, and extensive soft tissue injury. It becomes more challenging when peripheral vascular injuries have to be managed by orthopedic surgeons in absence of Vascular Surgeons. Ligation and amputation are routine in the Provincial hospital setup.Method: A total of 118 cases of all age and sex groups were included in the study. Only those patients were included who had extremity trauma with vascular injury which can be penetrating and blunt.Result: Peripheral vascular injuries after extremity trauma were more common in 21-40 (52.5%) age group and predominantly in Males (77.9%). Road traffic accidents were the most common cause accounting for 22.4% followed by physical assault by sharp weapon (20.5%). Isolated Ulnar artery was most commonly injured (25.2%) followed by Radial artery (16.8%). Popliteal artery injuries were seen in (8.41%). The commonest type of injury was Transection (65.4%) followed by Intimal injury/Contusion (13%). End-to-end anastomosis (54.2%) was the most common type of repair, followed by ligation (30.8%) and interposition vein graft in (10.2%). Complications were seen in 43.2%. Primary amputation was required in 16.1% of cases.Conclusion: Penetrating injuries were the most common injuries seen in our study with blunt injuries being common in lower extremity. Transection of vessel wall being common and end-to-end repair done by orthopedic surgeons was sufficient for the salvage of limbs irrespective of functional outcome. Early diagnosis, prompt resuscitation, and timely treatment given by primary surgeon irrespective of subspecialty training can save life and limb.